Exterior of the southern Garbhagriha of the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
The exterior of the southern garbhagriha (sanctum sanctorum) of the Mahakal Temple has a vedibandha (basal mouldings), jangha (wall) and shikhara (superstructure). The vedibandha mouldings are adorned and the jangha showcases bhadraratha (central vertical projection), intricately carved stambhas (buttresses) and jali (lattice) work. The shikhara of the temple is built in Shekhari style i.e., the central latina spires with rows of half spires added on either side.